Ultra‐light extensometer for the assessment of the mechanical properties of the human skin in vivo. Issue 4 (28th March 2017) - Jacquet, E.; Joly, S.; Chambert, J.; Rekik, K.; Sandoz, P.
Abstract : Background/purpose: This paper aims to present an ultra‐light extensometer device dedicated to the mechanical characterization of the human skin in vivo. Methods: The device developed was conceived to be non‐invasive, to work without any stand and to perform various uniaxial tensile tests with either effort or displacement control. We also use specific guarding tabs to make in vivo extension tests analogous to traction tests. Results: Force‐displacement curves are derived from the data provided by the device's sensors. The latter are converted into stress‐strain curves thanks to complementary measurements of the skin thickness. We present typical experimental data and results that demonstrate the device ability to built stress‐strain curves characteristic of the human skin behavior. An additional imaging unit records a sequence of images of the solicited skin area for further calculations of the displacement fields by digital image correlation. Conclusion: The analysis of the displacement and deformation fields validates the guarding tab efficiency and the capacity of the device to characterize the mechanical behavior of the human skin in vivo.